Peningkatan Proses Dan Hasil Belajar IPAS Menggunakan Model Pembelajaran Kooperatif Tipe Make A Match Berbantu Media Kartu Domino Pada Siswa Kelas IV SDIT Al-Akhyar - Jannati, Salsabillah; Megawati, Megawati; Guswita, Reni (Master of Pedagogy and Elementary School Learning, 2025)
This research is motivated by the learning process that is not optimal, the minimal use of teaching media used by teachers causes the learning process of science and natural sciences to be less enjoyable and the results of learning science and natural sciences have not reached the KKTP, which is 70. The purpose of this study is to describe the improvement of the process and results of IPAS by using Make A Match assisted by domino card media in the IV class of SDIT Al-Akhyar. This study uses a Classroom Action Research (CAR) design which is implemented in two cycles. One CAR cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects in this study were 18 students of class IV SDIT Al-Akhyar. Data collection techniques used observation, testing, and documentation techniques. Data collection instruments used observation sheet assessments and learning outcome test questions in implementing the Make A Match learning model assisted by domino card media. The results of the study using the Make A Match learning model assisted by domino card media can improve the process and results of learning science. This is evidenced by the results of the teacher's process observation sheet showing an increase in the learning process in cycle I showing a good category of 77.5% which increased in cycle II to a good category of 87.5%. The results of the assessment of the student learning process found an increase from the results of the observation sheet in cycle I showing a very poor category of 34% which increased in cycle II to a good category of 78%. Student learning outcomes in learning IPAS the Make A Match learning model assisted by domino card media in class IV SDIT Al-Akhyar showed an increase from cycle I, the percentage of student learning outcomes reached 50% which increased in cycle II to 78%.